L’Empire et la Révolution ou Bolivar et son double - Frédérique Langue (Caravelle)
Bolívar’s life and actions, hero of Latin American Independence Wars and and Venezuela’s « Liberator », gave rise from the nineteenth century onwards to the establishment of a civic religion whose consensual aspect accompanied the forming of the Venezuelan nation, paving the way for the imposition in the long term of an official History based on heroic cult. With Chávez’s arrival as President of the Republic (1999-2013), « Bolivar’s cult » reached a decisive stage. The new official History tends indeed to promote the redeeming vision of a « second Independence », this time against the American « empire », turning the « twenty-first century Bolívar » into the continent’s new saviour. Therefore, we are witnessing an unprecedented instrumentalization of History, in an extremely consensual and inspiring context: the Bicentennial of Latin American Independence Wars.